Aerial low-frequency hearing in captive and free-ranging harbour seals (Phoca vitulina) measured using auditory brainstem responses - Lucke, Klaus; Hastie, G.; Ternes, K.; McConnell, B.; Moss, S.; Russell, D.; Weber, H.; Janik, V. (Springer, 2016)
The hearing sensitivity of 18 free-ranging and 10 captive harbour seals (Phoca vitulina) to aerial sounds was measured in the presence of typical environmental noise through auditory brainstem response measurements. A focus was put on the comparative hearing sensitivity at low frequencies. Low- and mid-frequency thresholds appeared to be elevated in both captive and free-ranging seals, but this is likely due to masking effects and limitations of the methodology used. The data also showed individual variability in hearing sensitivity with probable age-related hearing loss found in two old harbour seals. These results suggest that the acoustic sensitivity of free-ranging animals was not negatively affected by the soundscape they experienced in the wild.